Managing customers profitably - Ryals, Lynette (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2008)
This book is a response to a need in the market place in the fast-growing field of customer profitability analysis and the profitable management of customer relationships. It combines innovative approaches to calculating the value of customers, with the management strategies necessary to make and keep customers profitable. It includes easy-to-follow instructions on how to calculate customer profitability, including worked examples (non-technical) and discusses strategies and their applications for organizations to manage customers profitably. Based on cases and feedback from the KAM Club and o.
10 The customer portfolio using both supplier and customer perspectives11 Risk; 12 Service-based segmentation; Section Three The strategic decisions that maximize the value of your customers; 13 Selective customer acquisition and retention; 14 The role of pricing in creating or destroying value; 15 Increasing customer equity using value propositions; Bibliography; Index.
Includes bibliographical references (pages 359-361) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Customer relations -- Management; BUSINESS & ECONOMICS -- Customer Relations; Customer relations -- Management